"Ideophones” in Upper Guinea Creoles - (:unkn) unknown (My University, 2019)
Like many Niger-Congo languages, all Upper Guinea Creoles (UGCs) spoken in Africa (i.e. except Papiamentu) make use of a specific set of adverbs which specifically intensify various verbs of the language. These ideophones have already been studied in some details for Guinea-Bissau Creole (Couto 1994, 1995, Doneux & Rougé 1988, Scantamburlo 1981, 1999, Kihm 1980, 1994) and briefly mentioned for Capeverdean (Quint 2000, 2008) and Casamance (Biagui 2018). However, quite often, the material published mainly consists of lists of items accompanied by rather short comments. In this presentation we intend to provide a broader overview of intensive ideophones across Upper Guinea Creoles, basing ourselves on first hand and published sources.First, drawing on typological references (Creissels 2002, 2006, Dingemanse 2012, 2018, Samarin 2001) and available data (in particular two unpublished lists of respectively 90 Casamance and 15 Capeverdean ideophones), we will endeavour to define the main phonological, syntactic and semantic characteristics of UGC ideophones. Second, we will develop a comparative approach, insisting both on what the different varieties have in common or not. Third, we will provide some insights about the origin of this interesting category which, like many other components of UGCs, has a double African and Portuguese provenience (e.g. Capverdean álbu < Portuguese alvo ‘white’ (variant of branco) and finu < Mandinka fǐŋ ‘black’). Finally, we will delve into the functional relationship between UGC ideophones and their Niger-Congo counterparts, with special emphasis on the substrate languages of UGCs, ie Mandinka, Wolof and other Atlantic languages.
Keywords: African Research